2009
DOI: 10.1097/wnr.0b013e32833017ce
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate agonist causes irreversible degeneration of inner hair cells

Abstract: Glutamate neurotoxicity in cochlear hair cells was investigated by administering the glutamate agonist alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) into the scala tympani of Mongolian gerbils. AMPA administration caused the formation of large number of vacuoles in the inner hair cells (IHCs) and dendritic terminals. The number of degenerated hair cells was counted using rhodamine-phalloidin and Hoechst 33342 staining. The administration of 50 microM AMPA caused reversible elevation of the audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…There have been reports showing glutamate cytotoxicity in hair cells [10,14] and one report suggested the aggravating actions of glutamate released from deteriorating hair cells, which supports our hypothesis [15]. This mechanism will also contribute to SGC destruction, which has been reported in homozygous (cir/cir) mice [4,12,13].…”
Section: Discussionsupporting
confidence: 86%
“…There have been reports showing glutamate cytotoxicity in hair cells [10,14] and one report suggested the aggravating actions of glutamate released from deteriorating hair cells, which supports our hypothesis [15]. This mechanism will also contribute to SGC destruction, which has been reported in homozygous (cir/cir) mice [4,12,13].…”
Section: Discussionsupporting
confidence: 86%
“…This treatment resulted in swelling of lateral-line afferent nerve terminals. This swelling was similar to what has been reported in mammal auditory system after AMPA exposure ( Puel et al, 1994 ; Hyodo et al, 2009 ). Functional calcium imaging revealed a loss of activity in afferent nerve terminals after this treatment.…”
Section: Noise Exposure Excitoxicity and Acquired Hearing Loss In Zesupporting
confidence: 91%
“…Subsequently, the afferent terminals swell and, in the case of KA application on auditory hair-cell explants, neurites retract ( Wang and Green, 2011 ). In cases of AMPA administration to inner ears, a small but significant percentage of inner hair cells are also lost 7 days following exposure ( Hakuba et al, 2003 ; Hyodo et al, 2009 ). Two recent pharmacological studies have used iGluR agonists to mimic noise exposure in zebrafish larvae.…”
Section: Noise Exposure Excitoxicity and Acquired Hearing Loss In Zementioning
confidence: 99%
“…There may be species-differences in the susceptibility of the hair cells to excitotoxic damage. For instance, in the rat, the hair cells were unscathed by the kainate insult (Juiz et al, 1989) but in the gerbil, the glutamate agonist AMPA was found to induce IHC death at high concentrations (Hyodo et al, 2009).…”
Section: Glutamatergic Excitotoxicitymentioning
confidence: 99%